Pemanfaatan Media Pembelajaran Berbasis Audio Visual Dalam Pengembangan Karakter Religius Siswa Di SD Citra Indonesia - Pradipta, Arel Dhea; P, Fuji Rahmadi (Innovative: Journal Of Social Science Research, 2025)
Learning media is one of the main factors in the learning process, media is a type of intermediary component, either in the form of humans, materials, or events, which can help students in acquiring knowledge, skills, and attitudes, this research aims at utilizing the use of audio-visual-based learning media in an effort to develop students' religious character at SD Citra Indonesia, with descriptive qualitative as a research method. The results show that the use of audiovisual media, such as learning videos, Islamic animations, and recorded lectures, can increase students' understanding and interest in religious material. This media plays a role in shaping students' religious character, however, there are challenges in its implementation, such as limited equipment and the readiness of teaching staff in managing learning technology. Therefore, support from the school is needed in providing adequate facilities and training for teachers so that the utilization of audiovisual media can be more optimal in building students' religious character.